ظاهرة الطّلاق في دولة الكويت أسبابها وآثارها وعلاجها في ضوء الشريعة الإسلامية - جاسم، جاسم أحمد عبد الله (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This research deals with the problem of divorce in the State of Kuwait, a social problem found in all societies of the Muslim world. Statistics showed a rise in the divorce rate in Kuwait amounted to thirty-five percent, which is a worrying and alarming percentage. This is the result of changes produced by the circumstances, economic and social conditions and modern means of technology and other things that have occurred in Kuwaiti society. Consisting of eight chapters and conclusion, this research highlights the meaning of ṭalaq (divorce) literally and terminologically, its pillars, wisdom, and types. It also explains the reasons for divorce in the State of Kuwait, including individual reasons related to each spouse, common reasons between them, and external reasons, as well as mentioned the objectives of Sharīʽah in the dissolution of marriage. The research investigated the psychological, social, economic and educational effects of divorce in the State of Kuwait, which had a negative impact on both who divorces and who is divorced and primarily on the children. Then the research suggested a remedy for the phenomenon of divorce in the State of Kuwait, which is related to its roots, before and after marriage in the light of Islamic law. The researcher used two approaches: inductive and descriptive analysis. Likewise, he conducted personal interviews with important segments related to the subject of research, and studied cases of divorce in Kuwait between 2011 and 2015 through the distribution and analysis of a questionnaire. The researcher also benefited from the experiences of others in the treatment of the phenomenon of divorce, such as the experience of Malaysia. This research reached several conclusions, the most important of which are: teaching the curricula related to the Muslim family and the Shariʽah objectives of marriage to students of institutes and universities helps to reduce the problem of divorce; the media and community institutions have an important role in highlighting the role of the family and its importance in society and protecting it from the disadvantages of globalization aimed at dismantling the family; and the application of strategies of countries with successful experience in reducing the problem of divorce spreading in their communities, helps to reduce that problem in Kuwait .